2023
DOI: 10.1002/eji.202250103
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental signals shaping NK‐cell reactivity in cancer

Bianca M. Balzasch,
Adelheid Cerwenka

Abstract: Since the postulation of the “missing‐self” concept, much progress has been made in defining requirements for NK‐cell activation. Unlike T lymphocytes that process signals from receptors in a hierarchic manner dominated by the T‐cell receptors, NK cells integrate receptor signals more “democratically.” Signals originate not only the downstream of cell‐surface receptors triggered by membrane‐bound ligands or cytokines, but are also mediated by specialized microenvironmental sensors that perceive the cellular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Adelheid Cerwenka (Heidelberg University, Medical Faculty Mannheim, Germany) is focusing on overcoming NK-cell dysfunction in the hostile TME. 42 Using scRNA-seq of NK cells isolated from RMA-S tumors, Cerwenka and her team found that NK cells up-regulate the hypoxia-inducible transcription factor HIF-1α. 43 Analysis of NK-cell functionality after culture in hypoxic conditions revealed reduced effector function, which prompted Cerwenka and her colleagues to investigate the role of HIF-1α in NK cells.…”
Section: Immune Escapementioning
confidence: 99%
“…Adelheid Cerwenka (Heidelberg University, Medical Faculty Mannheim, Germany) is focusing on overcoming NK-cell dysfunction in the hostile TME. 42 Using scRNA-seq of NK cells isolated from RMA-S tumors, Cerwenka and her team found that NK cells up-regulate the hypoxia-inducible transcription factor HIF-1α. 43 Analysis of NK-cell functionality after culture in hypoxic conditions revealed reduced effector function, which prompted Cerwenka and her colleagues to investigate the role of HIF-1α in NK cells.…”
Section: Immune Escapementioning
confidence: 99%
“…Overall, NKp30 + NK cells were enriched in renal carcinoma, but the inhibitory effect due to the altered NCR3 splice variants was predominant, which resulted in a NKp30-mediated NK cell cytotoxicity effect that was also deficient. Impaired NK effector function may be related to the potent immunosuppressive activity of the tumour microenvironment (TME) (36)(37)(38)(39). Such distinct expression of NCR3 splice variants is influenced by the cytokine microenvironment, which is extremely complex in vivo, especially in tumour tissues (40,41).…”
Section: Mediated Natural Killer (Nk) Cell Killing Function In the Pe...mentioning
confidence: 99%